Knowledge about Cervical Cancer and Pap Smear and the Factors Influencing the Pap test Screening among Women - Hossein Ashtarian; Elaheh Mirzabeigi; Elham Mahmoodi; Mehdi Khezeli (Shiraz University of Medical Sciences, 2017)
Background: Although the Pap smear is known as one of the effective methods to detect the cervical cancer, a large group of women are reluctant to do the test because of various reasons. Therefore, we carried out this study to determine the level of knowledge about cervical cancer and Pap smear and the factors influencing the Pap test screening among women. Methods: In this cross-sectional study, 355 women referred to the health centers of Gilan-e gharb city were randomly recruited in 2015. The participants asked to complete a self-administered questionnaire including five parts (questions about: demographic factors, knowledge about cervical cancer and Pap smear, Pap smear performance, barriers and facilitators related to Pap smear and the sources of information). Data were analyzed through SPSS version 19, using descriptive statistics, Independent T-test, and logistic regression. Results: The mean age of the participants was 34.08±7.81 years. Almost 50.4% of the subjects had a history of Pap smear test. Pap test performance was significantly higher in those who had higher knowledge (P<0.001). Knowledge about cervical cancer, Pap smear and age was the most important predictors of the Pap test performance (P<0.001). The most important barrier and facilitator to Pap smear test were inadequate knowledge and the recommendations received from family, friends and healthcare professionals (44.3% and 40.2%, respectively). Conclusion: Knowledge about Pap smear and cervical cancer was important in predicting Pap test doing. In addition, inadequate knowledge was introduced as the most important barrier to screening test from the perspective of women. Therefore, we suggest that health education and health promotion studies as interdisciplinary and targeted interventions should be implemented to improve the women's knowledge.